Factors affecting marketing decision making with an ethical content : collusive tendering in the construction contract market - Zarkada, Anna K. (My University, 1997)
Reports of immoral marketing practices i n the construction industry attract political, media and public but not much academic interest. This paper adopts a behavioural perspective and proposes a model for applying marketing ethics concepts and methods in the study of collusion in the construction contract market. An extensive multidisciplinary review of existing literature identified a lack of adequate conceptualisation of the mechanisms and decision making factors of collusive tendering. The process of developing the model is detailed in this paper. The objectives and methodology of the research project that tested the model are also outlined. The paper concludes with a brief note on the contributions and application of the proposed model.